Hierarchical adaptive control of safety buffers in manufacturing. Issue 13 (2019) - Wikner, J.; Hedvall, L.; Mattsson, S-A
Abstract: Buffer management is an important part of manufacturing planning and control where the safety buffers provide robustness in relation to uncertainty in demand and supply. Hierarchical control of safety buffers highlights the significance of decisions made at different levels and for different purposes with inter-level feedback and intra-level adaptation. A period-based view of time complements the hierarchical control by identifying inter-period and intra-period aspects of managing uncertainty and thereby promoting a proactive dominated or reactive dominated way of managing uncertainty. By combining these two inter vs. intra based concepts, a hierarchical approach to adaptive safety buffer control in manufacturing planning and control is outlined.